The Influence of Ethanol Extract of Leaves on Dragon Scales (Pyrrosia piloselloides) to the Histology of The Uterus Female Rats in vivo - Malangi, Setya Jenio; Holil, Kholifah (Proceedings of the International Conference on Green Technology; Vol 9 No 1 (2018): Proceeding of the 9th International Conference on Green Technology 2018, 2018)
The diversity of plants found in Indonesia is vast, and many are used for traditional medicine. One such plant is dragon scale ( Pyrrosia piloselloides ), which contains phytoestrogen compounds, such as flavonoids. These phytoestrogens can bind to estrogen receptors, producing estrogenic effects similar to endogenous estrogen. Therefore, a study was conducted to investigate the effect of ethanol extract of dragon scale leaves ( Pyrrosia piloselloides ) on the histology of the uterus of female white rats (Rattus norvegicus) in vivo. The research was experimental, using a completely randomized design (CRD). The treatments were grouped into six groups, each consisting of four female white rats. The treatments included a control group (no treatment) and rats given ethanol extract of dragon scale leaves ( Pyrrosia piloselloides ) with five different doses: 0 mg/200g body weight (P1), 25 mg/200g body weight (P2), 50 mg/200g body weight (P3), 75 mg/200g body weight (P4), 100 mg/200g body weight (P5), and 125 mg/200g body weight (P6). After administration, the rats' uterine organs were collected and prepared for histological observation with hematoxylin and eosin (HE) staining. The observed parameters were the number of endometrial glands and the thickness of the uterine layers. The results showed that the ethanol extract of dragon scale leaves ( Pyrrosia piloselloides ) affected the increase in the number of endometrial glands at doses of 25 mg/200g body weight up to 50 mg/200g body weight, but a decrease in the number of endometrial glands was observed at doses of 75 mg/200g body weight up to 100 mg/200g body weight. Meanwhile, the ethanol extract of dragon scale leaves ( Pyrrosia piloselloides ) did not affect the thickness of the endometrium, myometrium, and perimetrium in the histology of the female white rat uterus in vivo .